Evaluation of heat stress based on WBGT index and its relationship with physiological parameter of sublingual temperature in bakeries of Arak city - Mohsen Aliabadi; Mohammad Jahangiri; Maziyar Arrassi; Mehdi Jalali (طب کار)
Background: Exposure to high temperatures is common among workers in warm environments (especially in bakeries) which could cause some undesirable physiological effects. The aim of this study was to determine heat stress and its relationship with physiological parameter of sublingual temperature in workers employed in bakeries of Arak city. Methods: In this cross- sectional study, 126 workers employed in 63 bakeries in Arak was evaluated. Heat stress was evaluated based on WBGT (wet bulb globe temperature) index and physiological strain was evaluated based on sublingual temperature. The heat stress was measured using digital WBGT apparatus in workstations of the bakers and the bread dough co-bakers as the hottest places. Sublingual temperature of workers was measured using electronic sublingual thermometer. Data was analyzed using SPSS version 16 software. Results: In 76% of cases, heat stress exposed to workers based on WBGT index, was more than national recommended limit. Moreover, in 48% of cases, heat strain of workers based on sublingual temperature index was also more than the national recommended limit. The results showed significant difference between WBGT index in the bakeries based on baking technology type (traditional and mechanized bakeries) (p<0.001). The results showed significant difference between sublingual temperatures of workers in the bakeries based on baking technology type (p<0.001). Conclusions: Mechanization of bakeries could make notable effects on reducing the heat strain of workers. The significant relationship between WBGT index and sublingual temperatures of workers confirmed the reliability and generality of WBGT index for evaluating heat stress in bakeries.